Proposals for a National Health Service - Great Britain. National Health Service
1946-01 1946 1940s 16 pages Hospital and Specialist Services 5. This part of the service will cover the following field - (a) In-patient care in all types of hospital, including maternity homes, sanatoria, mental hospitals, mental deficiency institutions, convalescent homes and medical rehabilitation centres. (b) Out-patient care at out-patient departments of hospitals, and at specialist clinics associated with hospitals although not necessarily situated at them; including mental clinics, tuberculosis dispensaries, venereal disease clinics, eye clinics. (c) A consultant service of all kinds; based on the hospitals, but providing services not only at them but also at the patients' homes, where necessary, and at Health Centres, clinics, etc. Taking over the existing hospitals. 6. The ownership of the present public hospitals, voluntary and municipal, will be taken over by the Minister (subject to special arrangements in the case of the teaching hospitals, described in paragraph 12). Provision will be made for the protection of existing officers and servants. Buildings, equipment and other assets will vest in the Minister, and existing liabilities will be taken over. Where particular hospitals have hitherto been provided for particular classes or groups of patients only, it will be the aim - consistently with the rational planning of the new service - to retain the identity of the special purposes for which these hospitals have previously been supported, e.g., in a separate wing or other identifiable part of the organisation. Regional Hospitals Boards. 7. The country will be divided into about twenty natural areas or regions for hospital organisation. Each area will be based on one of the eleven university medical teaching centres - the natural focal points of specialist medicine and therefore of hospital services. 8. For each area or region there will be set up a Regional Hospitals Board appointed by the Minister and drawn from the major local authorities in the area, from local people selected by the Minister for their general suitability /for 292/847/4/83